Diaminds : Decoding the Mental Habits of Successful Thinkers - Moldoveanu, Mihnea C. (Book collections on Project MUSE., 2010)
Moldoveanu and Martin draw upon case studies and interviews - as well as theories and models from cognitive psychology, epistemology, analytic philosophy, and semiotics - to offer a new conception of successful intelligence that is immediately applicable to business situations.